The Impact of Secondary School Students’ Perceived Parenting Values on School Choice - Tódor, Imre (Central European Journal of Educational Research, 2023)
The target group of our quantitative research is comprised of secondary school students from Szeklerland (Romania). A multistage sampling was used: in the first stage students from all denominational schools were included, then students from the assigned non-denominational schools, while in the second stage we included students from the 9th and 11th grades (N=1927). A questionnaire was used as a data collection instrument. We were interested to find out which educational sector boasted most prominently the dimensions of autonomy and conformity values and whether they correlate with the decision-making process regarding the choice of school type.